MethSCAn: accurate exploratory analysis of single-cell methylomes: research briefing - Kremer, Lukas P. M. (Nature methods, 2024)
Single-cell bisulfite sequencing enables the genome-wide quantification of DNA methylation at single-cell resolution, but methods to analyze the resulting data are lacking. The MethSCAn software accurately distinguishes cell types and states by scanning the genome for informative regions and providing a robust approach to quantifying methylation within these regions.
Veröffentlicht am 31. Juli 2024
Gesehen am 26.11.2024
This is a summary of: Kremer, L. P. M. et al. Analyzing single-cell bisulfite sequencing data with MethSCAn. Nat. Methods https://doi.org/10.1038/s41592-024-02347-x (2024)